ChemInform Abstract: Copper(I)‐Catalyzed Dehydrogenative Amidation of Arenes Using Air as the Oxidant. Issue 33 (August 2015) - Li, Gang; Jia, Chunqi; Chen, Qingliang; Sun, Kai; Zhao, Feng; Wu, Hankui; Wang, Zhiyong; Lv, Yunhe; Chen, Xiaolan
Abstract The intermolecular dehydrogenative amidation of various arenes via C—H bond activation assisted by a 2‐pyridyl or 1‐pyrazolyl chelating group using air as the terminal oxidant is achieved using N‐aryl amides, N‐alkyl amides, benzamide derivative, imides, and lactams as coupling partners.